(untitled) (KONFERENSIYA, 2025)
This article examines the translation of phraseological units between closely related and distant languages, highlighting the strategies necessary to preserve both meaning and stylistic value. The study discusses common translation methods—equivalent, analogical, and calque (literal reproduction)—and emphasizes instances where none of these strategies are sufficient, requiring the use of descriptive translation